Aspects of creativity in adult animation: an overview of censorship and self-censorship in Western countries - Mitkus, Tomas (Creativity Studies, 2023)
Today, adult animation is the fastest growing segment in the industry. However, adult animation is also the least researched topic in animation field. In this article, the author explores what key elements hinder the growth in this animation segment with a focus on self-censorship and how it affects modern adult animation creative output and overall production. Also, the author discusses the concept of censorship in animation and its historical development. In other words, the genesis, and then reform of formal censorship systems into the age rating systems. And, while technically, with the abolition of the formal censorship system, today animators can create content of any kind, adult animation in the Western world has only begun to grow relatively recently. This paper investigates the key reasons that motivate self-censorship in animation to exist today, even when all the data shows that never before in the history of this medium, has the adult animation segment had such good conditions to get funded and reach an audience. Additionally, the author examines the concept of mature themes from the perspective of Western censorship apparatus.